Diseño de seguridad en la red de transporte de un sistema de medición de eficiencia energética para la Udla - Jácome Vásconez, Santiago Israel (2018)
Security in networks guarantee the functioning of the network and the flow of information. This proposal recommends the design of the network security for the project Energy Efficiency Analysis, which presents a productive solution to the consumption of energy for Universidad de las Américas in the campuses of Queri, Granados and Udlapark, by using energy sensors to obtain data in real time, which are transmitted wirelessly to a data base that is at the reach of the users remotely through a management software. This project is a network security design of a system to measure the productivity of energy at Udla. The objective is security, confidentiality, availability and integrity of data through the implementation of safety mechanisms and politics. Chapter 1. In this chapter theoretical information will be mentioned as well as current technologies that will allow us to create a design related to the project. Chapter 2. The next chapter will describe how the current information from the network is gathered. Chapter 3. In this final chapter we will design the solution for the network, taking a standard methodology as reference in order to obtain a safe and reliable network.